TRADISI BASAHA ISIFU DI DESA KASAKAMU KABUPATEN MUNA BARAT DAN RELEVANSINYA TERHADAP KEHIDUPAN BERMASYARAKAT - Sidiq, Muhamad Yusuf; Fauzi, Ahmad (Virtu: Jurnal Kajian Komunikasi, Budaya dan Islam, 2024)
This research aims to find out the meaning of the basaha isifu tradition in Kasakamu village, West Muna district. The basaha isifu tradition is one of the nisfu sya'ban traditions in Indonesia. At first glance, the basaha isifu in Kasakamu is different from the Nisfu Sya'ban tradition in other areas, both in terms of general matters and the meaning in it. Departing from this, this research aims to answer two basic problems. First, to find out how the basaha isifu tradition works in Kasakamu village, West Muna district. Second, to find out the symbolic meaning in the basaha isifu in Kasakamu village. This type of research is qualitative research, with data sources through interviews with local community leaders, of course not denying the literature related to nisfu sya'ban. The technique used in the data analysis process uses analytical descriptive techniques, using Clifford Geert's symbolic interpretive theory. The results of the research show, First, the process of the nisfu sya'ban tradition in Kasakamu village is different from others both with regard to the time of implementation, place of implementation and form of prayer. Second, the isifu wetness has three symbolic meanings in the isifu wetness tradition in Kasakamu village, Muna district West includes the meaning of religiosity, cultural meaning and social meaning.